PT Pertamina (Persero) Bertanggung Jawab terhadap Korban Kebakaran yang Disebabkan oleh Konsumen - Maulana, Galih Putra Mahendra; Rosando, Abraham Ferry (Journal Evidence Of Law, 2025)
This research aims to analyze PT Pertamina's legal responsibility in cases of fires caused by the use of their fuel products by consumers, by applying strict liability theory. This study uses normative juridical methods, referring to various statutory regulations, scientific journals and related legal literature. The research results show that PT Pertamina can be held legally responsible for fires that occur, without the need for direct proof of fault, based on the principle of strict liability. The application of this theory allows victims to claim compensation if it is proven that the product is not equipped with adequate safety guidelines, which violates consumer rights in accordance with the Consumer Protection Law. This study emphasizes the important role of PT Pertamina in educating consumers regarding the use of high-risk products, as well as the need for strict regulations in the safety aspects of fuel products to protect the public interest. The implication of this research is the need to strengthen company policies regarding efforts to prevent product hazards as well as increasing corporate social and ethical responsibility in minimizing the risk of fire.